Determinants of Bad Loans at Bank KBMI IV: Credit Restructuring Policies - Roro Rahajeng Kusumaningtyas; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to analyze the impact of GDP, interest rates, credit, LDR, ROA, restructuring policies, and the Covid-19 pandemic on NPL of KBMI IV banks in Indonesia during the periods before and after the implementation of credit restructuring policies. This study employs the Error Correction Model (ECM) method based on quarterly secondary data from Q1 2017 to Q4 2023. The results show that in the long term, GDP, LDR, ROA, and credit restructuring policies have a significant effect on NPL, while interest rates and the pandemic do not have a significant impact. In the short term, only LDR and ROA are proven to significantly affect NPL. These findings highlight the importance of internal banking policies and macroeconomic conditions in maintaining credit quality and the stability of the banking system, especially pandemic.